Do Old Age and Comorbidity via Non-Communicable Diseases Matter for COVID-19 Mortality? A Path Analysis - Goswami, Gour Gobinda; Mahapatro, Mausumi; Ali, A. R. M. Mehrab; Rahman, Raisa (Frontiers in Public Health, 2021)
This paper uses Our World data for COVID-19 death count, test data, stringency, and transmission count and prepares a path model for COVID-19 deaths. We augment the model with age structure-related variables and comorbidity via non-communicable diseases for 117 countries of the world for September 23, 2021, on a cross-section basis. A broad-based global quantitative study incorporating these two prominent channels with regional variation is unavailable in the existing literature. Old age and comorbidity are identified as two prime determinants of COVID-19 mortality. The path model shows that after controlling for these factors, one standard deviation increases in the proportion of persons above 65, above 70, or of median age raise COVID-19 mortality by more than 0.120 standard deviations for 117 countries. The regional intensity of death is alarmingly high in South America, Europe, and North America compared to Oceania. After controlling for regions, the figure is raised to 0.213, which is even higher. For old age, the incremental coefficient is the highest for South America (0.564), and Europe (0.314), which are substantially higher than in Oceania. The comorbidity channel via non-communicable diseases illustrates that one standard deviation increase in non-communicable disease intensity increases COVID-19 mortality by 0.132 for the whole sample. The regional figure for the non-communicable disease is 0.594 for South America and 0.358 for Europe compared to the benchmark region Oceania. The results are statistically significant at a 10% level of significance or above. This suggests that we should prioritize vaccinations for the elderly and people with comorbidity via non-communicable diseases like heart disease, cancer, chronic respiratory disease, and diabetes. Further attention should be given to South America and Europe, the worst affected regions of the world.